Inovasi administrasi kepegawaian dengan sistem aplikasi pelayanan kepegawaian (sapk) dalam mewujudkan good governance (studi pada badan kepegawaian daerah kota batu) - Nindry Septya Pranita (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2015)
Abstract: The Innovation of Employment Administration with Employment Service Application System in Creating Good Governance (Study on Civil Service Agency Kota Batu). Government policy on the implementation of electronic government in 2003 also emphasizes to use technology information in both national and local government agencies to be more comprehensive and integrated. Utilization of information technology in the field of employment aims to improve the effectiveness and efficiency in the field of data processing and employment information management, which can provide better, transparent and accountable employment services. Employment Service Application System is a form of government policies on e-government implementation made by BKN. There are many benefits of this information system, the ease and the speed are one of its benefits. The purpose of this study is to describe and analyze the implementation of the SAPK on KGB system online at BKD Batu. The BKD in Batu has conducted government regulations on the development of electronic government with developing Employment Service Application System in Batu government. The service system can facilitate employment administration services, so that employment services become excellent and fast. Keywords: Public Administration, Employment Administration, Electronic Government. Abstrak: Inovasi Administrasi Kepegawaian Dengan Sistem Aplikasi Pelayanan Kepegawaian (SAPK) dalam Mewujudkan Good Governance (Studi Pada Badan Kepegawaian Daerah Kota Batu). Kebijakan Pemerintah tentang implementasi electronic government tahun 2003 juga menganjurkan penggunaan IT di instansi pemerintah pusat maupun daerah, agar lebih komprehensif dan terintegrasi. Tujuan pemanfaatan IT adalah untuk meningkatkan efektivitas dan efisiensi dalam bidang Â pengolahan data dan pengelolaan informasi kepegawaian, sehingga dapat memberikan pelayanan kepegawaian yang lebih sempurna, transparan dan akuntabel. Sistem Aplikasi Pelayanan Kepegawaian merupakan bentuk kebijakan pemerintah tentang implementasi e-government yang dibuat oleh BKN. Banyak manfaat yang didapat dari sistem informasi tersebut, kemudahan dan kecepatan salah satu manfaatnya. Tujuan penelitian ini adalah untuk mendeskripsikan serta menganalisa pelaksanaan SAPK pada sistem KGB online di BKD Kota Batu. BKD Kota Batu telah melaksanakan peraturan pemerintah tentang pengembangan electronic government dengan mengembangkan Sistem Aplikasi Pelayanan Kepegawaian di lingkungan pemerintahan Kota Batu. Sistem pelayanan ini dapat mempermudah pelayanan administrasi kepegawaian, agar pelayanan kepegawaian menjadi prima dan cepat. Kata kunci: Administrasi Publik, Administrasi Kepegawaian, Electronic Government.